2018
DOI: 10.1038/s41418-018-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine signalling during ZEB1-mediated epithelial–mesenchymal transition augments local myofibroblast differentiation in lung fibrosis

Abstract: The contribution of epithelial-mesenchymal transition (EMT) to human lung fibrogenesis is controversial. Here we provide evidence that ZEB1-mediated EMT in human alveolar epithelial type II (ATII) cells contributes to the development of lung fibrosis by paracrine signalling to underlying fibroblasts. Activation of EGFR-RAS-ERK signalling in ATII cells induced EMT via ZEB1. ATII cells had extremely low extracellular matrix gene expression even after induction of EMT, however conditioned media from ATII cells un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
140
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 56 publications
6
140
0
1
Order By: Relevance
“…However, lineage tracing studies found the number of fibroblasts derived from epithelial cells to be small 43,44 , and these cells were not found to colocalise with α-SMA suggesting they did not transition to myofibroblasts 45,46 . It also been proposed in a number of systems that epithelial cells that have undergone EMT may secrete a range of fibrogenic growth factors and cytokines, with impaired epithelial repair leading to aberrant epithelial-mesenchymal communication contributing to the recruitment and activation of myofibroblasts 18,47,48 . Here, we show that autophagy inhibition in ATII cells can induce EMT, and this contributes to fibrosis via aberrant epithelial-fibroblast crosstalk, rather than as a direct contribution to the fibroblast population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, lineage tracing studies found the number of fibroblasts derived from epithelial cells to be small 43,44 , and these cells were not found to colocalise with α-SMA suggesting they did not transition to myofibroblasts 45,46 . It also been proposed in a number of systems that epithelial cells that have undergone EMT may secrete a range of fibrogenic growth factors and cytokines, with impaired epithelial repair leading to aberrant epithelial-mesenchymal communication contributing to the recruitment and activation of myofibroblasts 18,47,48 . Here, we show that autophagy inhibition in ATII cells can induce EMT, and this contributes to fibrosis via aberrant epithelial-fibroblast crosstalk, rather than as a direct contribution to the fibroblast population.…”
Section: Discussionmentioning
confidence: 99%
“…6a), indicating this effect is likely dependent on the cellular context. The importance of Snail2 in IPF has been demonstrated with Snail2 being upregulated in IPF lung epithelial cells, but not Snail1 or TWIST1, compared to control epithelial cells 16,18 . Jayachandran et al 54 reported that Snail2-mediated EMT may contribute to the fibroblast pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibroblasts, originated from exaggerated activation and abnormal differentiation of fibroblasts via EMT and FMT pathways, are widely considered as the effector cells responsible for fibrosis 33,34 . A prolonged inflammation, M2 macrophages differentiation and increased profibrotic factors, especially TGF-β1/Smad signaling form and maintain the microenvironment of fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous observations about the involvement of paracrine signalling during the EMT 11 , which could both coordinate the transition across a population of epithelial cells, and modulate the cells' microenvironment (eg. immunosuppression in cancer) [12][13][14] . Given this, we next established an experimental design to mechanistically assess the dependence of the EMT on paracrine signalling.…”
mentioning
confidence: 99%